The Use and Extent of Replacement Value Accounting in the Netherlands (Book). - Radebaugh, Lee H.; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "The Use and Extent of Replacement Value Accounting in the Netherlands," by R.K. Ashton.